Effects of β-sitosterol on growth, development and midgut enzymes of Helicoverpa armigera Hübner - Mishra, Monika; Sharma, Aarti; Dagar, Vinay Singh; Kumar, Sarita (Archives of Biological Sciences, 2020)
Paper description: Helicoverpa armigera is a global agricultural pest of serious concern. As repeated field application of chemical insecticides has caused negative impacts on the human health, non-targets and the environment, the effects of β-sitosterol, an eco-friendly bioactive phytocomponent, was investigated on H. armigera. larvae. Different concentrations of β-sitosterol were incorporated in the larval diet to assess the effects on larval growth and development, and midgut enzymes. Dietary β-sitosterol inhibited larval growth, affecting later instars and pupae more, pointing to cumulative effects of β-sitosterol. β-sitosterol can be used in Helicoverpa management programs. Abstract: Helicoverpa armigera is a global agricultural pest of serious concern. Continued use of chemical insecticides as control measures has raised grave health and environment concerns, necessitating a search for botanicals as safe alternatives. The current study investigates the effects of β-sitosterol, a bioactive phytocomponent in Thevetia neriifolia, on the growth and development, as well as on midgut enzymes of H. armigera. Dietary β-sitosterol produced dose-dependent systemic toxicity and growth inhibitory effects in H. armigera; the most significant effects were obtained with 10 µg/mL dietary β-sitosterol. Higher prepupal and pupal mortality in comparison to larval mortality and a comparatively greater reduction in average weight gained by later instars point to cumulative effects of β-sitosterol. The delayed effects were ascertained by the 82.05%-57.89% reduction in adult emergence in comparison to 95.02% emergence in controls. Dose-dependent effects of β-sitosterol were observed as significantly decreased enzyme activities of alanine aminotransaminase (ALT), aspartate aminotransaminase (AST) and alkaline phosphatase (ALP) in the larval midgut. Suppression of enzyme activity was obtained in the order ALT>AST>ALP. Impaired activity of gut enzymes possibly lowered the energy reserves and affected nutrient transport through the gut epithelium, affecting the growth and development of H. armigera. Our study points to a promising use of β-sitosterol against H. armigera, although further examination and field studies are needed to ascertain its possible use in control programs. https://doi.org/10.2298/ABS200308021M Received: March 8, 2020; Revised: April 28, 2020; Accepted: May 8, 2020; Published online: May 12, 2020 How to cite this article: Mishra M, Sharma A, Dagar VS, Kumar S. Effects of β-sitosterol on growth, development and midgut enzymes of Helicoverpa armigera Hübner. Arch Biol Sci. 2020;72(2):271-8.